A highly efficient catalytic material for degradation of antibiotics based on natural light and its preparation and application
The CTO@GO composite addresses the recombination issue in titanate perovskite by enhancing charge separation and adsorption, achieving efficient and stable antibiotic degradation under natural light, with high removal rates and non-toxic outcomes.
Patent Information
- Application Number
- CN202310898374.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-07-21
AI Technical Summary
Visible light-active titanate perovskite photocatalysts face challenges in industrial applications due to easy electron-hole pair recombination, limiting their degradation efficiency, and existing photocatalytic materials lack stability and efficiency in degrading antibiotics under natural light conditions.
A composite catalytic material composed of cubic calcium titanate (CTO) and graphene oxide (GO) is synthesized through a simple two-step process, utilizing a mass ratio of 85% CTO to 15% GO, which enhances charge separation and adsorption-photocatalytic synergy for effective degradation of antibiotics under natural light.
The CTO@GO composite demonstrates high degradation efficiency for antibiotics, achieving over 90% removal of florfenicol across various pH levels and maintaining stability through six cycles, with a wide applicability under different light sources, including sunlight, and produces non-toxic degradation products.
Smart Images

Figure CN117019130B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of environmental restoration and new pollutant control, and specifically relates to a high-efficiency catalytic material for degrading antibiotics based on natural light, and its preparation and application. Background Art
[0002] With the improvement of the quality of human life and the rapid development of science and technology, global water pollution and water shortage problems are becoming increasingly serious, and water resources are becoming more and more precious. At present, common water pollution treatment technologies include chemical precipitation, electrochemical degradation, membrane separation, photocatalytic degradation, biosorption, etc. Among them, photocatalytic degradation technology stands out among many water pollution treatment technologies due to its advantages such as simple operation, mild experimental conditions, ability to completely mineralize the substrate into non-toxic and harmless substances, and no secondary pollution.
[0003] Among the numerous photocatalysts, visible light-active titanate perovskite has excellent electronic structure, high efficiency of photogenerated electrons (e - ) and hole pairs (h + ), which greatly improves the utilization rate of sunlight. However, the e - / h + It is easy to compound, which is not conducive to its industrial application. Therefore, in order to improve the photodegradation activity of perovskite, scholars have modified it through various methods to improve the degradation efficiency.
[0004] In photocatalytic applications, carbon nanomaterials can suppress e - / h + Composite. As a carbon nanomaterial, GO has a two-dimensional planar structure, excellent mechanical strength and stability, excellent electrical conductivity, can effectively promote charge separation, and has good light transmittance in the visible and near-infrared regions. Due to these characteristics, GO has more advantages than other materials. Summary of the invention
[0005] The purpose of the present invention is to provide a high-efficiency catalytic material for degrading antibiotics based on natural light and its preparation and application, so as to solve the problems existing in the prior art.
[0006] A method for preparing a highly efficient catalytic material for degrading antibiotics based on natural light comprises the following steps:
[0007] (1) Calcium halide and nano-TiO2 are dissolved in an alkaline solution to obtain a mixed solution, which is then placed in a stainless steel autoclave, subjected to a high-temperature heat treatment at 180-220°C in a muffle furnace for 24-48 hours, washed multiple times, and then dried (preferably at 60°C) to obtain cubic calcium titanate;
[0008] (2) Mix and grind the cubic calcium titanate obtained in step (1) with GO.
[0009] Preferably, the mass ratio of calcium halide, nano-TiO2 and alkaline solvent is (1.5-2):1:(33-34):
[0010] Preferably, the mass ratio of GO to cubic calcium titanate is (0.05-0.2):(0.8-1). The mass ratio of GO to cubic calcium titanate is preferably 85% CTO:15% GO.
[0011] Preferably, the calcium halide is calcium chloride; and the alkaline solution comprises sodium hydroxide solution.
[0012] The preparation method mentioned above obtains a highly efficient catalytic material for degrading antibiotics based on natural light.
[0013] The above-mentioned high-efficiency catalytic material for degradation of antibiotics based on natural light is used for degradation of antibiotics.
[0014] The above-mentioned high-efficiency catalytic materials based on natural light degradation of antibiotics are used in sewage treatment.
[0015] A method for degrading antibiotics comprises the steps of: adding the above-mentioned high-efficiency catalytic material for degrading antibiotics based on natural light to an aqueous solution containing antibiotics for degradation reaction.
[0016] Preferably, the concentration of the high-efficiency catalytic material is 2 g / L.
[0017] Preferably, the light source for the degradation reaction may be one or more of a 400nm-760nm LED lamp, a 300W xenon lamp, and outdoor sunlight.
[0018] Preferably, the pH of the aqueous solution containing antibiotics is 2-11.
[0019] The calcium titanate preparation method of the present invention is simple to operate, does not need to adjust pH or control temperature, etc., and the temperature during the preparation process is relatively low, not exceeding 200° C. During the preparation process, photocatalysis does not need to be performed in an anaerobic / aerobic atmosphere.
[0020] The load is graphene oxide. Graphene oxide is a derivative in the process of graphite to graphene transformation. Compared with graphene, graphene oxide has richer functional groups, high chemical activity, high adsorption performance and coordinated photoelectric properties. Compared with graphene and reduced graphene, graphene oxide (GO) contains more abundant functional groups such as -OH, -COOH, -O-, etc. These functional groups give GO better dispersibility, hydrophilicity, chemical stability and interaction with polymers. These properties enable GO to better composite with calcium titanate and make GO better dispersed in water. The rich oxygen-containing functional groups allow it to better adsorb water pollutants.
[0021] Compared with the prior art, the CTO@GO of the present invention degrades new pollutants through the adsorption-photocatalytic synergistic effect under natural light. The rich functional groups of graphene oxide can effectively adsorb pollutants, making them closely adsorbed with the catalyst, and improving the removal rate of new pollutants by active free radicals in the photocatalytic process. In addition, the size of the cubic calcium titanate of the present invention is 20 to 30 nm, so that the electron-hole pairs have stronger redox ability, reducing the probability of hole-electron recombination, and greatly improving the catalytic activity. The photocatalyst of the present invention is non-toxic and harmless. After degradation, the fluoride ions are distributed on the surface of the catalyst, and the toxicity of the solution product after degradation is reduced, which is green and environmentally friendly. It can be widely used in the degradation of antibiotics. The preparation method of the present invention is simple, and CTO@GO can be synthesized by only two steps. The synthesis method is simple and does not require the addition of metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the appearance of CTO@GO;
[0023] Figure 2 is the scanning electron microscope image of CaTiO3;
[0024] Figure 3 is the X-ray powder diffraction pattern of the photocatalyst CTO@GO;
[0025] Figure 4 Zeta potential diagram of the photocatalyst CTO@GO;
[0026] Figure 5 is the cycling performance diagram of the photocatalyst CTO@GO;
[0027] Figure 6 The XPS spectra of the photocatalyst CTO@GO before and after degradation, where a is the C1s spectrum of the photocatalyst CTO@GO before and after degradation, b is the F1s spectrum of the photocatalyst CTO@GO before and after degradation, and c is the full spectrum of the photocatalyst CTO@GO before and after degradation;
[0028] Figure 7 EDS spectra of photocatalyst CTO@GO before and after degradation;
[0029] Figure 8 Figure 1 shows the free radical and hole trapping experiments.
[0030] Fig. 9 The pathway diagram of photodegradation of florfenicol by CTO@GO;
[0031] Fig.10 Fourier transform infrared spectra (FTIR) of CTO@GO before and after degradation;
[0032] Fig.11Effect of solution pH on the removal of florfenicol by commercial calcium titanate loaded with 15% GO (a), Effect of solution pH on the removal of florfenicol by CTO@15% GO photocatalyst (b), Performance of two different calcium titanate loaded graphene oxides in removing different antibiotics (c);
[0033] Fig.12 This is a relationship diagram of the effect of different GO addition amounts on the removal performance of florfenicol in the present invention;
[0034] Fig.13 This is a relationship diagram of the performance of removing florfenicol at different dosages of the present invention;
[0035] Fig.14 This is a graph showing the performance of the present invention in removing other antibiotics under different light source conditions. DETAILED DESCRIPTION
[0036] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0037] Example 1
[0038] A method for synthesizing an efficient catalytic material for degrading antibiotics based on natural light comprises the following steps:
[0039] (1) 0.3663 g of CaCl2, 0.2396 g of P25, and 8 g of NaOH were dissolved in 20, 20, and 40 mL of deionized water, respectively. The solutions were labeled A, B, and C, respectively. Then, B and C were added to A in sequence. The resulting mixed solution was placed in a muffle furnace for high-temperature treatment at 200°C for 24 h, then washed several times to remove impurity ions, and dried to prepare nanocubic calcium titanate.
[0040] (2) Grind and mix nanocubic calcium titanate and 15% GO (for example, to prepare 1 g of material, then 0.85 g CTO + 0.15 g GO) to obtain CTO@GO.
[0041] GO@CTO is used to degrade florfenicol, comprising: adding CTO@GO prepared in Example 1 to a 15 μM FF solution under a magnetic stirrer, adjusting the pH to 2, 7 and 10 respectively, with a CTO@GO dosage of 2 g / L, irradiating with 300 W and 15 A xenon lamp light sources for 12 hours respectively, centrifuging and collecting the supernatant after the reaction is completed, and monitoring the concentration change thereof with an ultraviolet spectrophotometer.
[0042] The appearance of the nanocubic calcium titanate, GO, and CTO@GO prepared in this example is as follows Figure 1 shown.
[0043] The scanning electron microscope image of calcium titanate prepared in this example is as follows Figure 2As shown in the left figure, the morphology is nanocubes with smooth surface and size of 20-30nm; the obtained CTO@GO is as follows Figure 2 As shown in the right figure, graphene oxide is uniformly loaded on the surface of nano cubic calcium titanate, which is applied to photochemical catalysis and can directly use visible light sources. In addition, the cubic calcium titanate prepared in this embodiment has a small size of only 20 to 30 nm, has a high efficiency in light utilization, and has a high degradation efficiency.
[0044] from Figure 3 From the XRD images, the highly efficient catalytic material CTO@GO based on natural light degradation of antibiotics in this embodiment was successfully prepared. The peak of the synthesized calcium titanate material was narrower and sharper, the signal was stronger, the crystal quality was good, the crystallinity was high, it had superior performance, and the photodegradation efficiency was higher. The signal peak of the XRD image of the composite graphene oxide calcium titanate material was significantly enhanced compared with that of the single material.
[0045] Figure 4 The Zeta potential shows that calcium titanate does not aggregate under acidic, alkaline or neutral conditions and has high stability. Its composite material with GO can effectively degrade new pollutants at pH 2-11. Fig.11 (b) The experimental data can prove that the degradation rate of CTO@GO for florfenicol is above 90% at different pH values, which proves that the CTO@GO of the present invention is acid- and alkali-resistant and has a wide range of applications.
[0046] Figure 5 The cyclic performance experiment shows that without replenishing the photocatalyst, the CTO@GO of the present invention can still achieve a 90% removal effect on florfenicol after six cycles of washing with acidic and alkaline solutions, maintaining a high photodegradation performance and showing excellent cyclic stability.
[0047] Figure 6 The XPS image shows that from the F1s image, 686.33eV is the potential of organic fluorine before degradation, and 689.5eV is the potential of inorganic fluorine after degradation, indicating that organic fluorine becomes inorganic fluorine after degradation; from the C 1s image, functional groups such as CF, C=O, CO, and CC change before and after degradation, indicating that the pollutant is decomposed into small molecules, achieving the purpose of non-toxic degradation.
[0048] Figure 7 The EDS image shows that after degradation, organic fluorine turns into inorganic fluorine and is distributed on the catalyst surface. The fluorine content on CTO@GO increases from zero to 1.06%. The results show that after degradation, fluoride ions remain on the catalyst surface and will not be discharged into the environment, reducing pollution to the environment.
[0049] Figure 8The free radical and hole capture experiments explained the basic mechanism of florfenicol degradation. The experimental results showed that h + 、O2 - and ·OH participated in the photocatalytic degradation reaction, ·O2 - It is the main active species. When the degradation reaction begins, florfenicol is adsorbed on the surface of the photocatalyst CTO@GO. When exposed to light, CTO@GO is excited by natural light to produce photogenerated - and h + , e - It reacts with dissolved oxygen in water to generate O2 - and ·OH, these active free radicals have strong oxidative ability and can degrade florfenicol.
[0050] Fig. 9 The molecular weight of florfenicol degradation products and possible degradation pathways were measured using liquid chromatography-mass spectrometry. The results showed that in addition to intermediates containing benzene rings and sulfur, some small molecules containing fluorine and nitrogen were also detected.
[0051] Combination Fig.10 Fourier transform infrared spectrum (FTIR) of the degradation product, compared with the spectrum before degradation, 3000cm -1 Left and right 767~860cm -1 The peaks at 1683, 1533 and 1149 cm disappeared or weakened, indicating that the benzene ring was cleaved; -1 The nearby peaks changed before and after degradation, which also confirmed that the C=O, NH and CF bonds were broken respectively. In summary, under the action of CTO@GO, florfenicol was decomposed into non-toxic and harmless small molecules through photolysis.
[0052] Example 2
[0053] The difference from Example 1 is that the GO addition amount of the prepared material is 5%, 10%, 15% and 20% respectively, and the CTO@GO addition amount is still 2g / L. A 300W, 15A xenon lamp light source is used to illuminate the 15μM FF solution for 12h. After the reaction is completed, the supernatant is centrifuged and the concentration change is monitored by ultraviolet spectrophotometer. The specific effects are as follows: Fig.12 As shown in the figure, the results show that the FF degradation rate of catalysts with different GO addition amounts is above 80%, among which CTO@15% GO has the best effect, and the removal rate of florfenicol is 100%. The composite effect of GO and CTO is "1+1>2". New pollutants are degraded through the adsorption-photocatalytic synergistic effect. The rich functional groups of graphene oxide can effectively adsorb pollutants, making them closely adsorbed to the catalyst, and improving the removal rate of new pollutants by active free radicals in the photocatalytic process.
[0054] Example 3
[0055] The difference from Example 1 is that the dosage of the prepared material CTO@15% GO is 0.5, 1.0, 2.0 and 5.0 g / L respectively, and the 15 μM FF solution is illuminated by a 300W, 15A xenon lamp light source for 12 h. After the reaction is completed, the supernatant is centrifuged and the concentration change is monitored by an ultraviolet spectrophotometer. The specific effects are as follows: Fig.13 As shown, the FF removal rate of the present invention is above 60%, and the degradation effect of 2.0g / L CTO@15% GO is the best. And by comparing with the experiment of adding catalyst under dark conditions, it is proved that the mechanism of action of the present invention is mainly photodegradation reaction, supplemented by adsorption.
[0056] Example 4
[0057] 1. The removal methods of other antibiotics based on the highly efficient catalytic material CTO@GO for natural light-degradation of antibiotics mainly include:
[0058] (1) The antibiotic aqueous solution was used as the pollutant water sample. Without adjusting the pH value, 2 g / L of the highly efficient catalytic material CTO@15% GO for natural light degradation of antibiotics prepared in Example 1 was added to the water sample; (2) the water sample was irradiated under a 300 W xenon lamp, 400 nm visible light and sunlight for 12 h, and water samples were taken at intervals;
[0059] (3) Filter the water sample with a membrane filter and monitor its concentration changes using an ultraviolet spectrophotometer.
[0060] In this example, the antibiotic pollutants include florfenicol, norfloxacin, azithromycin, clarithromycin, ciprofloxacin and carbamazepine, all at a concentration of 15 μM. Fig.14 shown.
[0061] 2. Degradation test results
[0062] (1) When the antibiotic pollutant is florfenicol, the degradation rate is 100% under a 300W xenon lamp; the degradation rate is 100% under 400nm visible light; and the degradation rate is 71.3% under sunlight.
[0063] (2) When the antibiotic pollutant is norfloxacin, the degradation rate is 66.8% under a 300W xenon lamp; the degradation rate is 70.3% under 400nm visible light; and the degradation rate is 43% under sunlight.
[0064] (3) When the antibiotic pollutant is azithromycin, the degradation rate is 90% under a 300W xenon lamp; the degradation rate is 86.5% under 400nm visible light; and the degradation rate is 37% under sunlight.
[0065] (4) When the antibiotic pollutant is clarithromycin, the degradation rate is 67.5% under a 300W xenon lamp; the degradation rate is 77.4% under 400nm visible light; and the degradation rate is 48% under sunlight.
[0066] (5) When the antibiotic pollutant is ciprofloxacin, the degradation rate is 90% under a 300W xenon lamp; the degradation rate is 69.3% under 400nm visible light; and the degradation rate is 59% under sunlight.
[0067] (6) When the antibiotic contaminant is carbamazepine, the degradation rate is 79% under a 300W xenon lamp; the degradation rate is 70% under 400nm visible light; and the degradation rate is 49% under sunlight.
[0068] Comparative Example 1
[0069] Commercial CTO@GO was obtained by grinding and mixing commercial calcium titanate and 15% GO, and the addition amount was 2 g / L. A method similar to Example 4 was used, using a 300W xenon lamp, to investigate the degradation effects of commercial CTO@GO and CTO@15% GO synthesized in Example 1 on florfenicol at different pH values. The results are as follows: Fig.11 As shown in (a) and (b): when the pH is 2, the degradation rate of commercial CTO@GO is 58.9%, and the degradation rate of CTO@GO synthesized by the present invention is 100%; when the pH is 7, the degradation rate of commercial CTO@GO is 56.2%, and the degradation rate of CTO@GO synthesized by the present invention is 100%; when the pH is 10, the degradation rate of commercial CTO@GO is 50.8%, and the degradation rate of CTO@GO synthesized by the present invention is 96%.
[0070] Comparative Example 2
[0071] Commercial CTO@GO was obtained by grinding and mixing commercial calcium titanate and 15% GO, and the addition amount was 2 g / L. A method similar to Example 4 was used, without adjusting the pH, and a 300W xenon lamp was used to explore the degradation effects of commercial CTO@GO and CTO@15% GO synthesized in Example 1 on other antibiotics. The results are as follows: Fig.11 (c)
[0072] (1) When the pollutant is norfloxacin, the degradation rate is 41.05% when the catalyst is commercial CTO@GO, and the degradation rate is 66.8% when the catalyst is CTO@GO synthesized by the present invention.
[0073] (2) When the pollutant is azithromycin, the degradation rate is 64.5% when the catalyst is commercial CTO@GO, and the degradation rate is 90% when the catalyst is CTO@GO synthesized by the present invention.
[0074] (3) When the pollutant is clarithromycin, the degradation rate is 50.4% when the catalyst is commercial CTO@GO, and the degradation rate is 67.5% when the catalyst is CTO@GO synthesized by the present invention.
[0075] (4) When the pollutant is ciprofloxacin, the degradation rate is 77.8% when the catalyst is commercial CTO@GO, and the degradation rate is 90% when the catalyst is CTO@GO synthesized by the present invention.
[0076] (5) When the pollutant is carbamazepine, the degradation rate is 61.05% when the catalyst is commercial CTO@GO, and the degradation rate is 79% when the catalyst is CTO@GO synthesized by the present invention.
Claims
1. A method for preparing a catalytic material for degrading antibiotics based on natural light, characterized in that: The following steps are involved: (1) Calcium halide and nano-TiO2 are dissolved in an alkaline solution to obtain a mixed solution, which is then placed in a stainless steel autoclave, subjected to high-temperature heat treatment at 180-220 °C in a muffle furnace for 24-48 h, washed several times, and then dried to obtain cubic calcium titanate CTO; (2) The cubic calcium titanate obtained in step (1) is mixed and ground with graphene oxide GO to synthesize CTO@GO.
2. The preparation method according to claim 1, characterized in that: The mass ratio of calcium halide, nano-TiO2 and alkaline solvent is (1.5~2):1:(33~34).
3. The preparation method according to claim 1, characterized in that: The mass ratio of GO to cubic calcium titanate is (0.05~0.2):(0.8~1).
4. A catalytic material for natural light-degradable antibiotics obtained according to the preparation method according to any one of claims 1 to 3.
5. The use of the catalytic material for natural light degradation of antibiotics according to claim 4, characterized in that: Used for the degradation of antibiotics.
6. A method for degrading antibiotics, characterized in that: The method comprises the steps of: adding the catalytic material for degradation reaction based on natural light degradation of antibiotics as claimed in claim 4 into an aqueous solution containing antibiotics.
7. The method for degrading antibiotics according to claim 6, characterized in that: The concentration of the catalytic material for natural light-based antibiotic degradation is 2 g / L.
8. The method for degrading antibiotics according to claim 6, characterized in that: The light source for the degradation reaction is one or more of a 400nm-760nm LED lamp, a 300W xenon lamp, and outdoor sunlight.
9. The method for degrading antibiotics according to claim 6, characterized in that: The pH of the aqueous solution containing antibiotics is 2-11.